2015
DOI: 10.1371/journal.pone.0141820
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Physicians' Attitudes and Knowledge on the Quality of Antibiotic Prescription: A Cohort Study

Abstract: Resistance increases with the use and abuse of antibiotics. Since physicians are primarily responsible for the decision to use antibiotics, ascertaining the attitudes and knowledge that underlie their prescribing habits is thus a prerequisite for improving prescription. Three-year follow-up cohort study (2008–2010) targeting primary-care physicians (n = 2100) in Galicia, a region in NW Spain. We used data obtained from a postal survey to assess knowledge and attitudes. A physician was deemed to have demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 26 publications
(34 reference statements)
4
67
0
6
Order By: Relevance
“…Noted that the main reasons for inappropriate use of antibiotics include physicians' lack of knowledge and training regarding antibiotics, non-adherence to treatment guidelines, uncertainty over the diagnosis, fear of clinical failure, and pressure from patients to prescribe antibiotics. (25) Results of the current study showed that participants' mean knowledge scores about antibiotics prescription for acute pharyngitis patients did not differ significantly according to their personal characteristics, having an antibiotics' prescription policy at PHCC or the application of that policy or according to attendance CME about antibiotics for acute pharyngitis. However, their knowledge differed significantly according to average daily patients' flow, 570 prescribing antibiotics for acute pharyngitis last week, and according to the used type of medical records system at PHCC and among those who read about prescribing antibiotics for acute pharyngitis.…”
Section: Results:-mentioning
confidence: 57%
See 1 more Smart Citation
“…Noted that the main reasons for inappropriate use of antibiotics include physicians' lack of knowledge and training regarding antibiotics, non-adherence to treatment guidelines, uncertainty over the diagnosis, fear of clinical failure, and pressure from patients to prescribe antibiotics. (25) Results of the current study showed that participants' mean knowledge scores about antibiotics prescription for acute pharyngitis patients did not differ significantly according to their personal characteristics, having an antibiotics' prescription policy at PHCC or the application of that policy or according to attendance CME about antibiotics for acute pharyngitis. However, their knowledge differed significantly according to average daily patients' flow, 570 prescribing antibiotics for acute pharyngitis last week, and according to the used type of medical records system at PHCC and among those who read about prescribing antibiotics for acute pharyngitis.…”
Section: Results:-mentioning
confidence: 57%
“…(18) Gonzalez et al (2015) supported the ability to modify prescriber physicians' knowledge and behavior , even it is a complex and difficult and includes several interventions, (e.g., continuing medical education through interactive group meetings, guidelines). (25) Andrajati et al (2017) emphasized that continuing educational programs and institution-specific guidelines are needed to improve physicians' knowledge regarding antibiotics prescription. (11) Limitations:-…”
Section: Results:-mentioning
confidence: 99%
“…Furthermore, ABS requires profound knowledge of local resistance Table 2 Results of four multivariate logistic regression models evaluating the independent influence of several study criteria on predetermined endpoints: (1) attendance of theoretical advanced training courses in the last 12 months (≥1 advanced training courses vs. no training courses), (2) self-reported quality of discharge letters regarding the documentation of MDRO and further outpatient arrangements (always vs. not always), (3) awareness of local ciprofloxacin-resistance rates in E. coli strains (correct category vs. wrong category) and (4) patterns, routine evaluation of antibiotic prescribing, and adherence to existing guidelines. In a recent study by Gonzalez-Gonzalez et al [7], poor theoretical knowledge derived from infrequent or lacking advanced training and was inversely associated with adequate guideline adherence in antibiotic prescribing. According to a study by Hansen et al [12], more than 25% of 40,000 patients received an antibiotic at 132 German hospitals; approximately 40% of these prescriptions were neither indicated nor justifiable.…”
Section: Discussionmentioning
confidence: 94%
“…After thorough literature review of similar studies and consulting acknowledged experts in the field (working committee "Infectious Diseases" of the German Association of Urology), the questionnaire was developed by the MR2 study group [6][7][8][9][10][11]. In a pilot study, 15 clinicians representing all included medical specialties completed the questionnaire, discussed and modified the items subsequently.…”
Section: Setting Participants and Survey Instrumentmentioning
confidence: 99%
See 1 more Smart Citation